Peculiarities of the formation of exocrine pancreatic insufficiency in patients with primary osteoarthritis under conditions of comorbidity - Halabitska, Iryna (Journal of Education, Health and Sport, 2023)
Summary. The comorbidity of primary OA and diseases of the gastrointestinal tract, which EPI accompanies, is an extremely relevant, complex, and unstudied problem of modern medicine, as it has a number of unsolved problems both in the treatment and rehabilitation of such patients. Common pathogenetic mechanisms of the progression of such comorbidity often have a mutually aggravating effect, which requires further study. The aim of the study is to analyze the changes in indicators of exocrine pancreatic insufficiency (EPI) in patients with primary OA under the conditions of comorbidity with diseases of the gastrointestinal tract (GI). Research material and methods. 304 patients with primary OA in comorbidity with diseases of the gastrointestinal tract accompanied by non-exacerbation EPI were examined. The comparison group consisted of 30 practically healthy individuals who did not have clinical, anamnestic, and instrumental signs of diseases of the gastrointestinal tract and joints. Results and discussion. It was established that in patients with primary OA in comorbidity with diseases that are accompanied by EPI, the levels of EPI indicators were statistically significantly different depending on the etiology of EPI. Conclusion. Post hoc analysis established the ranking of the pathology of the gastrointestinal tract, accompanied by EPI, according to the indicators of EPI in primary OA, which was located as follows, starting from the highest: CP ˃ T2DM ˃ chronic non-calculous cholecystitis and functional diseases of the gallbladder and biliary system ˃ chronic gastroduodenitis (p ˂0.05).